2020
DOI: 10.3892/etm.2020.9292
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA expression profiles significantly altered in UVA‑irradiated human dermal fibroblasts

Abstract: Circular RNAs (circRNAs) have been previously implicated in number of diseases. However, the roles of circRNAs in photoaging remain elusive. In the present study, to understand if photoaging influences the levels of circRNA expression, the expression of circRNAs in ultraviolet A (UVA)-irradiated human dermal fibroblasts were profiled. A total of 128 circRNAs were identified to be differentially expressed (fold change >1.5; P<0.05) after UVA exposure, including 39 upregulated and 89 downregulated circRNAs. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…We recently found that there were 128 differentially expressed circRNA in HDFs chronic light injury model through circRNA chip technology. Moreover, it was verified that circ_0011129 has anti-photoaging effect in HDF cells [ 25 ]. However, the instability in vivo and low delivery efficiency to the target cell limited their widely application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently found that there were 128 differentially expressed circRNA in HDFs chronic light injury model through circRNA chip technology. Moreover, it was verified that circ_0011129 has anti-photoaging effect in HDF cells [ 25 ]. However, the instability in vivo and low delivery efficiency to the target cell limited their widely application.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that circ_0011129 acts as a miR-6732-5p adsorption sponge to inhibit the reduction of type I collagen and the denaturation and accumulation of elastin in HDF exposed to UVA at the same time [ 25 ]. Consistent with previous studies, circ_0011129, delivered into HDF cells using 3D-sEVs, interfered with the process of cell photoaging by decreasing SA-β-gal activity, preventing the expression of MMP1, MMP3, and Cathepsin K, and accelerating the expression of collagen I, collagen III, and elastin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The candidate miRNAs and circRNAs interacting with CTSD mRNA were predicted with Arraystar homemade miRNA target prediction software based on TargetScan & miRanda. Also, differentially expressed circRNAs ( p ‐value < .05 and absolute fold‐change ≥ 1.5) were derived from our circRNA microarray dataset using the limma package in the R software 14 . The potential circRNAs associated with CTSD expression in photoaged fibroblasts were selected through the intersection of predicted circRNAs and our circRNA microarray profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the role of circRNAs in photoaging remains elusive. Our previous study has revealed an altered circRNA expression pattern in UVA‐induced photoaged dermal fibroblasts through performing the circRNA microarray analysis 14 . Which circRNA can regulate CTSD expression in photoaged fibroblasts is unknown.…”
Section: Introductionmentioning
confidence: 99%